Apuntes y reflexiones sobre el dolo y su regulación en el derecho penal ecuatoriano (Tema Central) - León González, Pablo Andrés (2023)
This article analyzes the current inclination of the ecuadorian legislator, to identify mens rea as an internal situation of the perpetrator, through the definition of knowledge and will in the Código Orgánico Integral Penal (COIP). This definition has generated two opposite consequences, on the one hand, the regression in the advance of mens rea to the current social traffic (negative), and on the other, the legal certainty afforded to the perpetrator (positive). From the analysis of these two consequences, it is recognized that ecuadorian criminal law opts for legal certainty. In this regard, a reflection on this particular issue is invited, with the aim of finding a way to legitimize this advance of mens rea in social traffic, without violating constitutional rights. To achieve this, as a first step, mens rea must be changed, through its normativization. Thus, through the use of an inductive and hermeneutic methodology, a work of legitimization of this normativization is undertaken, finally concluding in its viability. This is done without recognizing a fully standardized normativization, but also taking into account criteria that respect human dignity, through individual avoidability. Keywords: criminal law, subjective type, subjective imputation, mens rea, normativization, individual avoidability, constitutionalization, legal certainty.